2005
DOI: 10.1111/j.1365-2125.2005.02395.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of a single oral dose of telithromycin on sotalol‐induced qt interval prolongation in healthy women

Abstract: AimsTelithromycin belongs to ketolides, a new class of macrolide antibiotics. Macrolides are known to have the potential to prolong QT interval duration. Previous studies have shown that telithromycin did not induce significant QT interval prolongation in healthy subjects compared with placebo. The main objective of this study was to demonstrate the absence of amplification of QT interval prolongation induced by sotalol, when telithromycin and sotalol were co-administered. The secondary objective was to correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…3), and citrus juice inhibited oral absorption of at least acebutolol, atenolol and celiprolol in human 11–15. It was also reported that gastrointestinal absorption of sotalol was inhibited by coadministration of elithromycin 17. Thus, substantial transport by OATP‐A of β‐blockers (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…3), and citrus juice inhibited oral absorption of at least acebutolol, atenolol and celiprolol in human 11–15. It was also reported that gastrointestinal absorption of sotalol was inhibited by coadministration of elithromycin 17. Thus, substantial transport by OATP‐A of β‐blockers (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Oral absorption of atenolol and celiprolol was also reduced by orange juice 13, 15. Coadministration of therapeutic agents including verapamil and telithromycin has also been reported to reduce oral bioavailability of talinolol and sotalol, respectively 16, 17. One of feasible hypotheses may be that a certain constituents in the juice inhibits uptake process of these β‐blockers from apical side in the small intestinal epithelial cells, although such drug–food interactions may also be explained by other possibilities including inhibitory effect on gastric emptying rate and/or lowering effect on intestinal pH, leading to decrease in unionized form of β‐blockers.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest the increased oral bioavailability and reduced renal clearance to be caused by P-gp inhibition [ 185 ]. When sotalol was co-administered with telithromycin the sotalol C max decreased by 34% and AUC by 27%, leading to a decreased QTc interval by 15.5 ms [ 186 ]. Co-administration of ERY with talinolol resulted in a significant increase in talinolol AUC and C max [ 187 ], and co-administration with felodipine resulted in an increase of felodipine AUC and C max [ 188 ].…”
Section: Resultsmentioning
confidence: 99%
“…Telithromycin ist ein Opfer des Rifampicins. Ähnliche Wirkeinbußen von Telithromycin werden durch die gleichzeitige Gabe der CYP3A4 Induktoren Phenytoin, Carbamazepin und Phenobarbital, aber auch für Johanniskraut Präparate beschrieben[26][27][28].…”
unclassified